2016
DOI: 10.1111/coa.12730
|View full text |Cite
|
Sign up to set email alerts
|

A national analysis of trends, outcomes and volume–outcome relationships in thyroid surgery

Abstract: Objectives: Thyroid conditions are common and their incidence is increasing. Surgery is the mainstay treatment for many thyroid conditions, and understanding its utilisation trends and morbidity are central to improving patient care. Accepted ArticleThis article is protected by copyright. All rights reserved. Results: Mean age at surgery was 49±30 and a female predominance (82%) was observed.Most patients underwent hemithyroidectomy (51%) or total thyroidectomy (32%). Patients underwent surgery for benign (52.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 9 publications
6
40
1
Order By: Relevance
“…There are also limitations to our study that relate to the influence of clinical coding subjectivity, variability and error on the accuracy of the English administrative big data. In order to reduce this influence, we eliminated all patients with unclear‐type thyroidectomies and aggregated codes into a small number of clinical entities to increase specificity . Conversely, using temporally linked data did allow index thyroidectomy to be linked to late complications regardless of which hospital they occurred in, and under whose care the patients were subsequently admitted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also limitations to our study that relate to the influence of clinical coding subjectivity, variability and error on the accuracy of the English administrative big data. In order to reduce this influence, we eliminated all patients with unclear‐type thyroidectomies and aggregated codes into a small number of clinical entities to increase specificity . Conversely, using temporally linked data did allow index thyroidectomy to be linked to late complications regardless of which hospital they occurred in, and under whose care the patients were subsequently admitted.…”
Section: Discussionmentioning
confidence: 99%
“…Post‐operative disorders of calcium homeostasis and vocal palsy were defined as post‐operative if they were coded in the index thyroidectomy and as late if they were identified during a subsequent admission, as previously defined. Annual surgeon volume was dichotomised at 30 based on our earlier findings . Follow‐up was calculated as the most recent attendance at outpatients or a hospital admission, and time from index procedure to the occurrence of specific events such as placement of gastrostomy tube, emergency admission to hospital, hospital admission with acute lower respiratory tract infection were used as actuarial outcome variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the usually inadequate endocrine surgical training during residency, surgery residents wishing to practice endocrine surgery may benefit from additional training in their final year or dedicated fellowship training [14]. Many studies published in recent years showed a relationship between hospital/surgeon volume and patient outcomes which highlights the importance of advanced postgraduate training in endocrine surgery [78][79][80][81][82][83]. Two years of additional fellowship training in thyroid and endocrine surgery is now being advocated by an increasing number of national endocrine surgical associations as the best way to prepare surgeons for society's needs for highly skilled, competent thyroid surgeons of the future [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate lower complication rates (hypocalcemia, nerve injuries, bleeding, and surgical site infections) as well as shorter lengths of stay for surgeons performing a high volume of thyroid operations in comparison to low volume surgeons. [17][18][19][20] Adam and colleagues looked at almost 17,000 patients from the National Inpatient Sample and determined that a surgeon volume threshold of >25 total thyroidectomies per year was associated with decreased complications and shorter hospital stays. 21 Another group compared financial costs of high versus low volume surgeons considering both cost of complications and cost of hospital stay.…”
Section: High-volume Surgeons Have Better Outcomesmentioning
confidence: 99%